Augmenting Aquaculture Production in Sewage-Fed Village Ponds through Regulated Growth of Water Hyacinth, Eichhornia crassipes (Mart.) Solms - CHAUDHARI, AJIT KESHAV; Chandra Kanta Misra; Sunil Kumar S Ail; Rathindra Nath Mandal (Fishery Technology, 2023)
The freshwater aquaculture activities in Gujarat State, India are mostly carried out in the village ponds leased to the fish farmers through the Village Pond Fisheries policy, 2003. Domestic sewage from households is continuously fed to the village pondsnresulting in excessive growth of aquatic weeds. This study describes the effect of aquatic macrophyte, Eichhornia crassipes (Water hyacinth) management in sewage-fed aquaculture ponds in three districts of Gujarat namely Vadodara, Anand, and Kheda. Advanced fingerlings (yearlings) of Indian Major Carps and exotic carps (100-150 g) were stocked @ 5000 no./ha. E. crassipes was maintained at an extent of 5-10 % water area of the pond. Monitoring of water quality, growth, and health of fish were recorded bimonthly from three locations viz., the inlet of sewage entering to pond (L1), mid location of pond (L2), and the farthest location of pond (L3). The analysis of data showed that the water pH and dissolved oxygen showed an increasing trend at L2 and L3 locations when compared with L1 while other parameters such as total alkalinity, total hardness, total ammoniacal nitrogen, nitrite, nitrate, phosphate, BOD, COD, and TDS decreased. Fish production was estimated to be 3.1±0.17 MT/ha over a period of 8 months. This research will aid in the management of water quality in aquaculture ponds fed by sewage.